Ascent into Heaven in Luke-Acts : New Explorations of Luke's Narrative Hinge - Pao, David W.; Bryan, David K. (Book collections on Project MUSE., 2016)
Luke's two-volume work contains the only narrative depictions of Jesus' ascent into heaven in the New Testament. The significance of the event at the end of the Gospel and the beginning of Acts have long been recognized. While select studies have focused on particular aspects of these accounts, however, the importance of the ascension to Luke-Acts calls for renewed attention to the narratological and theological significance of these accounts. Here, leading scholars discuss the ancient, literary and theological contexts of the ascent-into-heaven accounts for the next generation of interpreters.